PERANAN SUMBER DAYA MANUSIA UNTUK MENDUKUNG MENINGKATKAN PRODUKTIFITAS PENELITIAN BIDANG PENERBANGAN PADA PUSAT PENELITIAN DAN PENGABDIAN MASYARAKAT DI SEKOLAH TINGGI PENERBANGAN INDONESIA - Pribadi Asih (Politeknik Penerbangan Indonesia Curug, 2019)
The research was aimed at finding out: first the background that made human resources of lecturer and the lower productivity in the field of aviation. Second, the steps that should be taken in solving such problems. Third, formulation that had been constructed by Pusat PPM STPI in improving productivity in the field of aviation. Data of the research had been collected though a qualitative methode by interviewing STPI lectures and, or researchers as informan. It had been found that most of informan were very low in research productivity due to various reasons. It could be because of their low interest in that field or they got less incentives compare that they obtained in teaching. Besides, a number of them still faced some problem in research methodology. It was suggested that unit PPM STPI should take an active role in improving the productivity of research in the field of aviation by conducting seminar, training, workshop, and other activities. Pusat PPM STPI should have strategic, planning for focusing on the environmental problems and involving more lectures and, or researchers progressing researchs. It is expected that in future more lectures and, or researchers would take active role in the field of research or other scientific activities..